Natural Products: A Promising Therapeutics for Targeting Tumor Angiogenesis - Li, Ruyi; Song, Xin; Guo, Yanan; Song, Peng; Duan, Dongzhu; Chen, Zhe-Sheng (Frontiers in Oncology, 2021)
Tumor-associated angiogenesis is a key target for anti-cancer therapy. The imbalance between pro-angiogenic and anti-angiogenic signals elicited by tumor cells or tumor microenvironment always results in activating “angiogenic switch”. Tumor angiogenesis functions in multi-aspects of tumor biology, including endothelial cell apoptosis, tumor metastasis, and cancer stem cell proliferation. Numerous studies have indicated the important roles of inexpensive and less toxic natural products in targeting tumor angiogenesis-associated cytokines and apoptotic signaling pathways. Our current knowledge of tumor angiogenesis is based mainly on experiments performed on cells and animals, so we summarized the well-established models for angiogenesis both in vitro and in vivo. In this review, we classified and summarized the anti-angiogenic natural agents (Polyphenols, Polysaccharides, Alkaloids, Terpenoids, Saponins) in targeting various tumor types according to their chemical structures at present, and discussed the mechanistic principles of these natural products on regulating angiogenesis-associated cytokines and apoptotic signaling pathways. This review is to help understanding the recent progress of natural product research for drug development on anti-tumor angiogenesis.